Woman, nation, food: Domesticity and the imperial project in “Ladies' Home Journal” food advertising, 1898–1899 - Monrreal, Sahar H. (University of Minnesota, 2008)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: Business History and gender